PENDUGAAN STOK KARBON DI KAWASAN HUTAN PENDOPO GUBERNUR KOTA PONTIANAK - Baruna, Tomi; Astiani, Dwi; Darwati, Herlina (JURNAL HUTAN LESTARI, 2017)
Forest is a natural resource that is very important and beneficial for life and living either directly or indirectly. This study aims to determine how much carbon is stored, in the area of Forest City Hall Governor Pontianak. The method used in this study, is non-destructive sampling method with recording the diameter of all the trees on the track 20 m wide and 100 m long using allometric equation appropriate for estimating biomass. Based on the research results of carbon estimation stored in Governor City Hall Forest area with 3.2 ha area there are 38 species of trees with the number of 584 individuals, biomass about 140.62 tons/ha, while for carbon stock from stands about 70.27 tons/ha. Keywords: carbon stock, forest city